1992
DOI: 10.1042/bj2840491
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptors on cultured astroglial cells. Kinetic and pharmacological characterization of oxytocin-binding sites on intact hypothalamic and hippocampic cells from foetal rat brain

Abstract: The ability of astroglial cells to exhibit oxytocin (OT)-binding sites has been investigated in embryonic hypothalamic and hippocampic astroglial cell cultures. The differential characteristics of binding of OT and [Arg8]vasopressin (AVP) agonists and antagonists to the OT-binding sites using the highly selective iodinated OT antagonist d(CH2)5-[Tyr(Me)2,Thr4,Tyr-NH2(9)]OVT ([125I]OTA) have been evaluated using intact cells maintained for 12 days in culture. The specific binding displayed features of reversibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 58 publications
3
20
2
Order By: Relevance
“…Recently, Scofield and colleagues (2015) demonstrated that specific activation of astrocytes (via Gq coupled DREADDs) in NAcore decreased cued reinstatement of cocaine seeking through an mGluR2/3-dependent mechanism. Here, we speculate that the localization of astroglial oxytocin receptors reduces relapse via Gq signaling that can activate transduction pathways including IP3 receptors and the release of intracellular calcium stores resulting in glial transmitter release, including glutamate (Di Scala-Guenot et al, 1994; Di Scala-Guenot and Strosser, 1992; Hamilton and Attwell, 2010). Extrasynaptic glutamate can thereby activate mGluR2/3 receptors located presynaptically on cortical glutamatergic axons, inhibiting synaptic release of glutamate, thus restoring glutamatergic tone (Moussawi and Kalivas, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Scofield and colleagues (2015) demonstrated that specific activation of astrocytes (via Gq coupled DREADDs) in NAcore decreased cued reinstatement of cocaine seeking through an mGluR2/3-dependent mechanism. Here, we speculate that the localization of astroglial oxytocin receptors reduces relapse via Gq signaling that can activate transduction pathways including IP3 receptors and the release of intracellular calcium stores resulting in glial transmitter release, including glutamate (Di Scala-Guenot et al, 1994; Di Scala-Guenot and Strosser, 1992; Hamilton and Attwell, 2010). Extrasynaptic glutamate can thereby activate mGluR2/3 receptors located presynaptically on cortical glutamatergic axons, inhibiting synaptic release of glutamate, thus restoring glutamatergic tone (Moussawi and Kalivas, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, resolution obtained with the autoradiography does not allow precise localization of receptors on a specified cell type. By contrast, using embryonic hypothalamic cultures, it has been possible to detect and characterize OT receptors both on neurones (Di Scala-Guenot et al, 1990) and astrocytes (Di Scala-Guenot and Strosser, 1992). Their pharmacological characteristics were similar to those already described for the OT receptors in central (Elands et al, 1987) and peripheral (Elands et al, 1990;Soloff et al, 1989) membrane preparations.…”
Section: Introductionmentioning
confidence: 89%
“…
ABSTRACTA recent study demonstrated oxytocin (OT) receptors on hypothalamic cultured astrocytes (Di Scala-Guenot and Strosser, 1992). The attempt in the present paper was to determine a possible intracellular calcium mobilization induced by OT receptor activation in these cells.
…”
mentioning
confidence: 98%
“…In this study, we have not determined the source of oxytocin and the location of its receptors responsible for the E GABA shifts. Whether the activation of oxytocin receptors in MNCs (Freund-Mercier et al, 1994) or nearby glial cells (Di Scala-Guenot and Strosser, 1992;Di Scala-Guenot et al, 1994) by oxytocin from the dendrites of MNCs (Ludwig, 1998) leads to the shifts is open for additional investigation.…”
Section: Discussionmentioning
confidence: 99%